Principles and labs for physical fitness - Hoeger, Werner W. K.; Hoeger, Sharon A. (Cengage Learning, 2016)
Helps you discover the benefits of an active, healthy lifestyle. Emphasizing behavioral modification approaches, the authors challenge you to improve your life with cardiovascular exercise, strength training, better nutrition, weight management, and overall wellness